ROLE OF GEN ITALIA IN THE IDENTIFICATION OF MELANITIS SPECIES (LEPIDOPTERA : SATYRIDAE) - ROSE, H.S.; SHARMA, NARENDER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
Out of three species known to occur in India i.e., leda Linnaeus, phedima Stoll and zitenius Herbst referable to genus Melanitis Fabricius, the former two species have been re-examined. The structures of the male and female genitalia have been interpretted along with reporting of variations in wing maculation.